Personal finance: a study involving Accounting Sciences course students - Santos, Lorrana Vitoreto dos (2023)
The objective of the study is to analyze the planning and management capacity of personal finances of Accounting students at the State University of the Midwest (UNICENTRO), at Campus Santa Cruz. For the development of this study, a descriptive research was carried out, with a quantitative approach. The sample comprised 152 Accounting students, and the data were submitted to descriptive statistics, analysis of variance (Anova) and linear regression. The findings indicate that having children significantly reflects on the preference for credit. With regard to managing income and expenses and short-term vision, it was found that households with more people have a significant relationship. It was observed that family groups in which income ranges from R$ 3,001.00 to R$ 5,200.00 have a significant relationship in the short-term view of these academics, thus, it is inferred that planning is directed only to the short term term.